Comparative study of protozoan parasite communities between Anabas testudineus and Channa punctatus - Bhuiyan, Md Aminul Islam; Kabita, Fatima Nahar; Jhinu, Zannatun Nahar; Bhuiyan, Md Hamim (Dhaka University Journal of Biological Sciences, 2021)
The study was conducted to determine the comparative occurrence of protozoan parasites of two host species- Anabas testudineus and Channa punctatus. The host fishes were collected from April, 2018 to March, 2019 from freshwater bodies of Mymensingh, Kishoreganj, Faridpur and Jashore districts of Bangladesh. Three species of myxozoa (Henneguya mystusia, Henneguya qadrii and Henneguya acerinae) and four genera/species of ciliophora (Trichodina acuta, Trichodina sp., Epistylis lwoffi and Amphileptus disciformis) in A. testudineus; three genera/species of myxozoa (Henneguya chaudhuryi, Henneguya bengalensis and Myxobolus sp.), three species of ciliophora (Trichodina pediculus, Epistylis lwoffi and Apisoma piscicolum) and a few actinosporean stage of myxoza in C. punctatus were identified. The prevalence of protozoan infections were found higher in A. testudineus (76.19%) compare to C. punctatus (51.72%). However, mean intensity was relatively higher in C. punctatus (95.93 ± 41.53) than that of A. testudineus (71.38 ± 32.26). Myxozoans were clearly dominant group in both hosts. Multiple parasitic infections were higher in A. testudineus. The highest parasitic infection was observed in Mymensingh (100%) and lowest in Jashore (40%) in A. testudineus, whereas it was highest in fish of Faridpur (100%) and lowest in Mymensingh (33.33%) in C. punctatus. Shannon Diversity Indices indicated that the parasite community was poorly diverged in both hosts of all study areas. However, Simpson’s Diversity revealed that, parasites community was moderately diverged in both hosts in Mymensingh and in other study areas they were poorly diverged. Dhaka Univ. J. Biol. Sci. 30(1): 23-34, 2021 (January)